2008
DOI: 10.1523/jneurosci.0582-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of Metabolic and Neurovascular Responses to Levodopa in the Treatment of Parkinson's Disease

Abstract: We compared the metabolic and neurovascular effects of levodopa (LD) therapy for Parkinson's disease (PD). Eleven PD patients were scanned with both [ O]-H 2 O and [18 F]-fluorodeoxyglucose positron emission tomography in the unmedicated state and during intravenous LD infusion. Images were used to quantify LD-mediated changes in the expression of motor-and cognition-related PD covariance patterns in scans of cerebral blood flow (CBF) and cerebral metabolic rate for glucose (CMR). These changes in network acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
218
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(243 citation statements)
references
References 57 publications
23
218
2
Order By: Relevance
“…The administration of clinically effective doses of levodopa to PD patients and normal controls has been shown to produce diffuse increases in CBF without changes in oxygen utilization, suggesting cerebrovascular dilation (Leenders et al, 1985). A similar dissociation between CBF and glucose metabolism has been found on a regional basis after levodopa administration in PD subjects (Hirano et al, 2008). In general, stimulation of the dopamine system increases CBF (Leenders et al, 1985).…”
Section: Discussionmentioning
confidence: 71%
“…The administration of clinically effective doses of levodopa to PD patients and normal controls has been shown to produce diffuse increases in CBF without changes in oxygen utilization, suggesting cerebrovascular dilation (Leenders et al, 1985). A similar dissociation between CBF and glucose metabolism has been found on a regional basis after levodopa administration in PD subjects (Hirano et al, 2008). In general, stimulation of the dopamine system increases CBF (Leenders et al, 1985).…”
Section: Discussionmentioning
confidence: 71%
“…The region of hyperperfusion in the globus pallidus in patients is in keeping with previous findings of elevated glucose metabolism in this region. 43 However, it may also be related to L-DOPA medication which has been shown to increase CBF in this region, 44,45 particularly as the hyperperfusion is greatest in the PIGD group of whom a greater proportion were on L-DOPA medication (table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Using positron emission tomography (PET), Hirano et al, 2008 have found that the administration of L-DOPA causes a much larger increase in putaminal and pontine regional cerebral blood flow (rCBF) in PD patients experiencing dyskinesia compared with non-dyskinetic subjects. No difference in cerebral metabolic rate (CMR) for glucose was found on L-DOPA, pointing to a large dissociation between blood flow and glucose metabolism in dyskinetic patients (Hirano et al, 2008). The relationship between changes in rCBF and the angiogenesis induced by L-DOPA is presently unclear, but these phenomena are likely to share some common molecular and chemical determinants.…”
Section: Discussionmentioning
confidence: 99%